Recognizing oesophageal intubation: successful use of the oesophageal detector device combined with a disposable end-tidal carbon dioxide detector - Bothma, Pieter Adriaan (My University, 2016)
Unrecognized oesophageal intubation leads to death or severe disability. Even careful, well trained anaesthetists may be unable to differentiate tracheal from oesophageal intubation by the commonly employed methods. End-tidal carbon dioxide measurement has been found to be a reliable test of tracheal intubation. The availability of a small disposable end-tidal carbon dioxide detector, the Easy cap makes this facility universally available. The oesophageal detector device is a small mechanical device used to recognize oesophageal intubation. By combining two reliable devices working on completely different principles the risk of false negative or false positive results are virtually eliminated. The potential defects of each device are covered by the other. The purpose of this study was to evaluate the combined use of the oesophageal detector device and the Easy cap by a blinded observer to differentiate the endotracheal tube from an oesophageal tube in sixty patients. These two tests were found to be very reliable, easy, rapid and cheap - ideal for use in theatre, casualty departments and in the field. The advantages and disadvantages of these devices are discussed and the relevant literature is reviewed.
A dissertation to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Medicine (in the branch of Anaesthesia). Johannesburg 1994.
Keywords: Intubation, Intratracheal; Esophagus